Transformation of regional system of rural settlement of Zaporizhia region in the post-soviet period - Nelipa, Kseniia (Human Geography Journal, 2017)
As a result of strengthening of globalization and transition ofUkraineto the market economy the regional settlement system have changed. Considerable changes were tested by the network of rural settlements of industrial regions, such as the Zaporizhia region. Therefore determination of modern tendencies and problems of functioning of the regional systems of rural settlement of this area became a necessity. For the Zaporizhia area characteristic middle level density of settlement network. It is predefined by the late settling of territory, the development of industrial centers, the lack of drinking-water and relatively arid climatic conditions in the region. As a result of the outflow rural population to urban areas, in the last 25 years, the amount and density of rural population in the districts of region significantly decreased. Since1945 inthe Zaporizhia region from an account 260 rural settlements were removed from the register. Most of them were eliminated in the period from 1960 to 1970 – period of intensive industrialization of the region. One of the reasons of removal of rural settlements from the register is their unification (205 settlements). Compensative processes in relation to formation of new rural settlements were insignificant (14 settlements). On quantitative parameters the network of rural settlements in the Zaporizhia region in a post-soviet period did not almost change. However on this time there is a process of reduction to the amount of population in these settlements. This situation demonstrates the continuing depopulation of rural settlements. The amount of small villages with a population of less than 100 persons is increasing and the amount of rural settlements of between 100 to 1,000 persons is reducing. The amount of "endangered" villages (less than 50 persons) in the overall share of rural settlements of the region is 12.8%. There is polarization in development of network of rural settlements in the region. Thus, to solve the above mentioned problems is necessary to conduct the socio-economic and administrative-territorial reform in rural areas. It is needed to improve the classification of rural settlements on the quantity of population, to develop ways of revival of small forms of territorial organization of rural settlements in the region.